Fatigue problems of transmission belts: - Emri, Igor (Materiali in tehnologije, 2006)
We performed an analysis of the time-dependent behaviour of drive belts under the loading conditions to which they are exposed during normal operation. Theyare dynamically loaded with a tooth-like periodic (cyclic) load. Within each loading cycle the elastomeric material undergoes a combination of creep and retardation processes. Under certain conditions, the retardation process between two loadings cannot be fully completed. Thus, the material enters the second phase of loading with a residual strain state. Consequently, the strain state starts to accumulate, which leads to hardening of the material, crack formation, and ultimately to the failure of the belt. We recognized that drive belts exhibit the accumulation of strain when exposed to normal operation at certain critical angular velocities. The strain accumulated in each consecutive cycle depends on the geometry of the belt, the angular velocity of the pulleys, the number of completed cycles, and the retardation spectrum of the material. In this paper we discuss the effect of the number of loading cycles to which the material is exposed in the strain-accumulation process. For a given belt geometry the critical angular velocity increases with the number of loading cycles. At the same time the magnitude of the accumulated strain decreases non-linearly as the number of loading cycles increases. Hence, the strain-accumulation process slows down with the increasing number of loading cycles. However, if the belt operates at, or in the close vicinity of, its critical angular velocity, it will almost certainly fail. Since the critical angular velocity is directly related to the retardation time of the material, and the magnitude of the accumulated strain depends on the strength of the corresponding discrete spectrum lines, we can conclude that the time-dependent mechanical properties of the elastomersic material from which the belt is constructed are the most critical parameters for predicting the durability of drive belts and other dynamically loaded elastomeric products.
Keywords: jermeni; utrujanje; viskoelastična analiza; deformacije; elastomeri